Severe Acute Respiratory Syndrome Coronavirus Associated Myocarditis - Wantania, Frans E. N.; Wowor, Ribka E.; Tandiawan, Ridwan (Open Access Macedonian Journal of Medical Sciences, 2021)
Myocardial injury is common in patients with coronavirus disease 2019 (COVID-19). Among COVID-19 related myocardial injuries, etiology may vary, including myocarditis, myocardial infarct, sepsis-associated myocardial injury, and/or stress-induced cardiomyopathy. More data from prospective cohorts and case series are needed to understand the exact mechanism of COVID-19 associated myocardial injuries. It is clinically suspected that myocarditis is the cause of myocardial injury. However, myocarditis has a heterogeneous clinical presentation and tends to be underdiagnosed in critically ill COVID-19 patients. Due to the potential of rapid deterioration in the patient’s condition, it is imperative to recognize myocarditis as a sequel to COVID-19, and a multidisciplinary team should be formed for managing all clinically suspected patients with COVID-19 associated myocarditis. Further studies are needed to recognize better and understand the relationship between myocarditis and COVID-19.